The Effectiveness of the Implementation of the Local Government Digitalization Program in Increasing Local Original Income in South Bolaang Mongondow Regency - Paputungan, Mohamad Dicky A.; Darmawati, Darmawati; Makkulawuzar, Kingdom (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to analyze the effectiveness of the implementation of the digitalization program implemented by the Regional Government of South Bolaang Mongondow Regency in order to increase Regional Original Revenue (PAD). Government digitalization is part of efforts to reform bureaucracy and regional financial transparency which is expected to improve the efficiency of public services and optimize regional revenue. The research method used is an empirical juridical approach with data collection techniques through literature studies, observations, and interviews with local government officials and related parties. The results of the study show that the implementation of digitalization, such as regional tax information systems and electronic-based licensing services, makes a positive contribution to increasing PAD. However, its effectiveness is still constrained by technical factors such as uneven technological infrastructure, low digital literacy of apparatus, and limited supporting regulations. Therefore, it is necessary to strengthen regional legal policies, increase human resource capacity, and synergy between institutions to support the sustainability of digitalization programs. These findings provide important implications for the development of regional administrative laws and the formulation of digital-based fiscal policy strategies